Int Arch Med Microbiol 2018
DOI: 10.23937/iamm-2017/1710002
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Adherence to Antiretroviral Therapy among HIV Infected Patients in Nyamagana-Mwanza, Northern Tanzania: A Cross Sectional Study

Abstract: Background: High level of Antiretroviral Therapy adherence among HIV infected patients contributes to better treatments outcome and has additional importance in preventing the development of drug resistance. It also improves the quality of life and makes the patient live longer and healthier. The objective of the study was to determine level of adherence as well as factors influencing adherence to antiretroviral therapy among HIV infected patients in Nyamagana district, Mwanza, Tanzania.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 19 publications
(36 reference statements)
2
4
0
Order By: Relevance
“…While our sample size was sufficient to estimate the proportion of ART non-adherence among participants, only a limited number of covariates appeared to have an association with non-adherence and could be considered as potential predictors-age, education, and alcohol consumption. Our findings are similar to those of other studies that found age [52,53], education [19,54,55] and alcohol consumption [56] as factors associated with ART non-adherence. Nonetheless, our findings differ from studies that found ART non-adherence to be associated with side effects of the drugs, social isolation and complexity of the antiretroviral (ARV) regimens [57]; physical, economic and emotional stress [49]; poor or inability to follow prescribed treatment, no visits in a month, anxious and or depressed mood, difficulty in taking medication, cannabis consumption and receiving methadone treatment [58]; and being a female sex worker and suffering from moderate-to-severe depression [52].…”
Section: Plos Onesupporting
confidence: 92%
“…While our sample size was sufficient to estimate the proportion of ART non-adherence among participants, only a limited number of covariates appeared to have an association with non-adherence and could be considered as potential predictors-age, education, and alcohol consumption. Our findings are similar to those of other studies that found age [52,53], education [19,54,55] and alcohol consumption [56] as factors associated with ART non-adherence. Nonetheless, our findings differ from studies that found ART non-adherence to be associated with side effects of the drugs, social isolation and complexity of the antiretroviral (ARV) regimens [57]; physical, economic and emotional stress [49]; poor or inability to follow prescribed treatment, no visits in a month, anxious and or depressed mood, difficulty in taking medication, cannabis consumption and receiving methadone treatment [58]; and being a female sex worker and suffering from moderate-to-severe depression [52].…”
Section: Plos Onesupporting
confidence: 92%
“…For PLWHA, factors related to gender dimensions, socioeconomic factors such as education status, income, asset possession and food security have been associated with non-adherence to ART ( Basti et al, 2017 ; Abera et al, 2015 ; Alagaw et al, 2013 ). For example, in South Africa ( Eyassu, Mothiba & Mbambo-Kekana, 2016 ), Cameroon ( Fonsah et al, 2017 ) and northern Tanzania ( Samuel Edward et al., 2018 ), gender, income and level of education were reported as the determinants of ART adherence. Another study in Wolaita Sodo, Ethiopia, found lack of food was associated with poor adherence ( Alagaw et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, participants strategically timed their medication intake, often scheduling it at night to avoid stigma and enhance privacy. From the previous studies, PLWH hide their medications or miss doses to avoid suspicion about their HIV status ( Holtzman et al, 2015 ; Molla et al, 2018 ; Samuel Edward et al, 2018 ; Weaver et al, 2014 ). These actions, viewed through the lens of resilience engineering, can be seen as adaptive responses to navigate and overcome societal barriers.…”
Section: Discussionmentioning
confidence: 99%